High-conductivity composite solid electrolyte membrane and preparation method and application thereof

By using a highly conductive composite solid electrolyte membrane composed of lithium salt, inorganic nanofiber membrane and polyethylene oxide in lithium batteries, the safety problem of liquid electrolyte in lithium batteries is solved, and higher conductivity and machinery are achieved Strength reduces the risk of thermal runaway and improves the safety performance of the battery.

CN119481243APending Publication Date: 2025-02-18DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES

Patent Information

Application Number
CN202510057000.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing lithium batteries use liquid electrolytes to risk solutions leakage and flammability and explosion, and a safer solid electrolyte is needed to replace them.

Method used

Using a highly conductive composite solid electrolyte membrane composed of lithium salt, inorganic nanofiber membrane and polyethylene oxide, the inorganic nanofiber membrane is prepared by electrospinning and high-temperature calcination, and the lithium salt and polyethylene oxide are cast to the inorganic In the nanofiber membrane, a highly conductive composite solid electrolyte membrane was obtained by vacuum drying.

Benefits of technology

It improves the conductivity and mechanical strength of the composite solid electrolyte membrane, reduces the risk of thermal runaway in the battery, improves safety performance, and is suitable for all-solid-state lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a high-conductivity composite solid electrolyte membrane and a preparation method and application thereof. Belongs to the solid-state battery field. The high-conductivity composite solid electrolyte is prepared from a lithium salt, an inorganic nanofiber membrane serving as a network framework and polyethylene oxide (PEO) serving as a high polymer matrix, the thickness of the film is 20-50 [mu] m; the lithium salt is selected from at least one of LiTFSi, LiFSi and LiClO4; the molecular weight of the polyethylene oxide is 200000 to 2000000 g / mol; the wire diameter of the inorganic nanofiber membrane is 300-600 nm, and the thickness of the inorganic nanofiber membrane is 15-40 [mu] m.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a highly conductive composite solid electrolyte membrane and a preparation method and application thereof, and belongs to the field of solid-state batteries. Background Art

[0002] Lithium-ion batteries are widely used as power sources for various mobile devices due to their high energy density, high operating voltage, no memory effect, and long cycle life. From 2017 to 2022, global lithium battery shipments increased from 160GWh to 1080GWh, and China's share increased from 33% to 83%. It is expected that global lithium battery shipments will reach 2347GWh in 2025, of which China will account for about 89%. However, most existing lithium batteries use liquid electrolytes, which are prone to solution leakage and are flammable and explosive. Therefore, improving the safety of existing lithium batteries is an urgent problem to be solved.

[0003] Solid electrolytes are the best choice to solve the current flammable and explosive problems of lithium batteries. According to existing reports, solid electrolytes such as oxides, sulfides, and polymers have been developed. However, the above-mentioned single solid electrolytes still have many problems. For example, although the oxides have high conductivity, the interface performance is poor. Sulfides are structurally unstable and easy to swell, have many side reactions, and the preparation process will cause environmental pollution. Polymer electrolytes are composed of polymers and lithium salts. Due to their light weight, good mechanical flexibility, and excellent processing performance, they have received widespread attention. Low room temperature ionic conductivity is their main defect. Composite solid electrolytes are composed of inorganic-polymers, combining the advantages of both types of materials. They have become a research hotspot and the direction of commercialization efforts in recent years. Summary of the invention

[0004] In view of the deficiencies in the prior art, one of the objectives of the present invention is to provide a highly conductive composite solid electrolyte membrane.

[0005] According to one aspect of the present application, a highly conductive composite solid electrolyte membrane is provided, characterized in that: The highly conductive composite solid electrolyte consists of lithium salt, an inorganic nanofiber membrane as a network skeleton and polyethylene oxide as a polymer matrix.

[0006] The thickness of the highly conductive composite solid electrolyte membrane is 20-50 μm.

[0007] The lithium salt is selected from at least one of LiTFSi, LiFSi, and LiClO4.

[0008] The molecular weight of the polyethylene oxide is 200000-2000000 g / mol.

[0009] The inorganic nanofiber membrane has a diameter of 300-600 nm and a thickness of 15-40 μm.

[0010] The size effect of the inorganic nanofiber membrane can reduce the crystallinity of the polymer, promote the movement of the PEO polymer chain segments, and improve the conductivity of the composite solid electrolyte membrane. In addition, it also improves the mechanical strength of the PEO solid electrolyte membrane. At the same time, the porous structure of the inorganic nanofiber membrane is also conducive to the transmission of lithium ions and improves ion conductivity.

[0011] The inorganic nanofiber membrane is obtained by the following steps: The organic polymer template, the inorganic material and the solvent are mixed to obtain an electrospinning solution, which is charged into a syringe for electrospinning, and calcined under an air atmosphere to obtain the inorganic nanofiber membrane.

[0012] The organic polymer template is selected from at least one of polyvinyl alcohol and polyvinyl pyrrolidone.

[0013] The inorganic material is selected from at least one of silicon dioxide, zirconium oxide and titanium dioxide.

[0014] The solvent is selected from water and / or ethanol.

[0015] In the electrospinning solution, the concentration of the organic polymer template is 6-12 wt %, and the concentration of the inorganic material is 2-4 times the concentration of the organic polymer template.

[0016] The voltage of the electrospinning is 15-30KV.

[0017] The extrusion speed of the electrospinning is 1.5-3 ml / h.

[0018] The receiving distance of the electrospinning is 8 to 25 cm.

[0019] The calcination temperature is 600-1000°C.

[0020] The calcination time is 2 to 8 hours.

[0021] The electrospinning process uses a high-throughput jet remote-field control integrated array electrospinning nozzle module and core components to achieve mass production of high-uniformity diaphragms. It also has a macro sensor detection system to 100% avoid missed sprays and wrinkles, and achieve defect-free production of diaphragms.

[0022] According to another aspect of the present application, a method for preparing the above-mentioned highly conductive composite solid electrolyte membrane is provided, comprising the following steps: The lithium salt, polyethylene oxide and an organic solvent are mixed to obtain a membrane-forming slurry, which is then cast into an inorganic nanofiber membrane, allowed to stand, and vacuum dried to obtain the highly conductive composite solid electrolyte membrane.

[0023] The organic solvent is selected from at least one of acetonitrile and dichloromethane.

[0024] In the film-forming slurry, the mass content of polyethylene oxide is 2-6 wt %, and the mass content of lithium salt is 2-6 wt %.

[0025] The vacuum drying temperature is 40-60°C.

[0026] The vacuum drying time is 12 to 36 hours.

[0027] According to another aspect of the present application, there is provided an application of the above-mentioned high-conductivity composite solid electrolyte membrane for use in an all-solid-state lithium battery.

[0028] The beneficial effects of this application include: (1) The present invention provides a composite solid electrolyte membrane, which includes an inorganic nanofiber membrane skeleton, a lithium salt and a PEO polymer matrix, wherein the size effect of the inorganic nanofiber membrane can reduce the crystallinity of the polymer, promote the movement of the PEO polymer chain segments, and improve the conductivity of the composite solid electrolyte membrane. The porous structure of the inorganic nanofiber membrane is also conducive to the transmission of lithium ions and improves the ionic conductivity. The lithium salt further improves the ionic conductivity. At the same time, the inorganic nanofiber membrane also improves the mechanical strength of the PEO solid electrolyte membrane. In short, under the joint cooperation of the various components, the solid electrolyte membrane of the present invention has a high ionic conductivity and good stability.

[0029] (2) The present invention provides a method for preparing a composite solid electrolyte membrane, including preparing an inorganic nanofiber membrane by electrospinning and high-temperature calcination, and casting a polymer solution containing lithium salt. The electrospinning process uses a high-throughput jet remote-field control integrated array electrospinning nozzle module and core components to achieve batch manufacturing equipment for high-uniformity diaphragms, and has a micro-sensor detection system to 100% avoid leaks and wrinkles, achieve defect-free production of diaphragms, and significantly improve safety.

[0030] (3) The present invention provides an application scenario of a composite solid electrolyte membrane, which is ultimately applied to the field of solid-state batteries. There is no flowing electrolyte in the battery system, and there is a composite solid electrolyte membrane with good thermal stability, thereby reducing the risk of thermal runaway of the battery under abuse and improving safety performance. DETAILED DESCRIPTION

[0031] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0032] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0033] Example 1 Preparation of highly conductive composite solid electrolyte membrane.

[0034] 1) Dissolve 2g of polyvinyl alcohol in 7g of deionized water, dissolve 5.85g of TEOS + 0.0473g of oxalic acid as a silica precursor in 4.10g of deionized water, and mix the two liquids evenly to obtain an electrospinning solution; 2) Adding the electrospinning solution into the syringe, electrospinning was performed under the conditions of voltage of 18 kV, extrusion speed of 2.5 ml / h, and receiving distance of 15 cm; collecting the inorganic nanofiber membrane containing the polymer material; 3) The material obtained in step 2 above was placed in a muffle furnace and calcined at 800°C for 4 hours in an air atmosphere to obtain an inorganic nanofiber membrane with a diameter of 300 nm and a thickness of 20 µm; 4) Take 0.2 g of PEO with a molecular weight of 500,000 g / mol and disperse it in 9.4 g of acetonitrile, add 0.4 g of lithium salt LiTFSi to the solution to obtain a slurry, cast the slurry into the inorganic nanofiber membrane obtained in step 3, let it stand, and vacuum dry it at 45°C for 20 hours to obtain a highly conductive composite solid electrolyte membrane with a thickness of 25 µm.

[0035] Example 2 Preparation of highly conductive composite solid electrolyte membrane.

[0036] 1) Dissolve 1.47g polyvinyl pyrrolidone in 7g ethanol solvent, and dissolve 5.85g TEOS + 0.0473g oxalic acid as silica precursor in 4.10g deionized water solvent. Mix the two liquids evenly to obtain an electrospinning solution. 2) Adding the electrospinning solution into the syringe, electrospinning was performed under the conditions of voltage of 25 kV, extrusion speed of 2 ml / h, and receiving distance of 13 cm; collecting the inorganic nanofiber membrane containing the polymer material; 3) The material obtained in step 2 above was placed in a muffle furnace and calcined at 600°C for 2 hours in an air atmosphere to obtain an inorganic nanofiber membrane with a diameter of 450 nm and a thickness of 15 µm; 4) Take 0.2 g of PEO with a molecular weight of 500,000 g / mol and disperse it in 9.4 g of acetonitrile, add 0.4 g of lithium salt LiTFSi to the solution to obtain a slurry, cast the slurry into the inorganic nanofiber membrane obtained in step 3, let it stand, and vacuum dry it at 45°C for 20 hours to obtain a highly conductive composite solid electrolyte membrane with a thickness of 20 µm.

[0037] Example 3 Preparation of highly conductive composite solid electrolyte membrane.

[0038] 1) Dissolve 2g of polyvinyl pyrrolidone in 7g of deionized water, add 6g of zirconium acetate as a precursor of zirconium oxide into 2.0g of deionized water, and mix the two liquids evenly to obtain an electrospinning solution; 2) Adding the electrospinning solution into the syringe, electrospinning was performed under the conditions of voltage of 15 kV, extrusion speed of 1.5 ml / h, and receiving distance of 25 cm; collecting the inorganic nanofiber membrane containing the polymer material; 3) The material obtained in step 2 above was placed in a muffle furnace and calcined at 1000°C for 8 hours in an air atmosphere to obtain an inorganic nanofiber membrane with a diameter of 600 nm and a thickness of 40 µm; 4) Take 0.6 g of PEO with a molecular weight of 200,000 g / mol and disperse it in 8.8 g of dichloromethane, add 0.6 g of lithium salt LiFSi to the solution to obtain a slurry, cast the slurry into the inorganic nanofiber membrane obtained in step 3, let it stand, and vacuum dry it at 40°C for 36 hours to obtain a highly conductive composite solid electrolyte membrane with a thickness of 50 µm.

[0039] Example 4 Preparation of highly conductive composite solid electrolyte membrane.

[0040] 1) Dissolve 1g of polyvinyl alcohol in 7.5g of solvent ethanol, and dissolve 2g of tetrabutyl titanate, a titanium dioxide precursor, in 6.2g of solvent ethanol. Mix the two liquids evenly to obtain an electrospinning solution. 2) Adding the electrospinning solution into the syringe, electrospinning was performed under the conditions of voltage of 15 kV, extrusion speed of 2 ml / h, and receiving distance of 18 cm; collecting the inorganic nanofiber membrane containing the polymer material; 3) The material obtained in step 2 above was placed in a muffle furnace and calcined at 700°C for 3 hours in an air atmosphere to obtain an inorganic nanofiber membrane with a diameter of 400 nm and a thickness of 20 µm; 4) Take 0.2g of PEO with a molecular weight of 2000000g / mol and disperse it in 9.4g of acetonitrile, add 0.4g of lithium salt LiClO4 to the solution to obtain a slurry, cast the slurry into the inorganic nanofiber membrane obtained in step 3, let it stand, and vacuum dry it at 60°C for 12h to obtain a highly conductive composite solid electrolyte membrane with a thickness of 25µm.

[0041] Comparative Example 1 0.2 g of PEO with a molecular weight of 500,000 g / mol was dispersed in 9.4 g of acetonitrile, and 0.4 g of lithium salt LiTFSi was added to the solution to obtain a slurry. The slurry was cast, allowed to stand, and dried in vacuum at 45°C for 20 h to obtain a PEO solid electrolyte membrane with a thickness of 25 µm.

[0042] Performance Test 1: The solid electrolyte membranes prepared in the above embodiments and comparative examples were subjected to puncture strength and room temperature conductivity tests. The specific test methods are as follows. The test results are shown in Table 1.

[0043] Puncture strength: The puncture strength is tested using a universal tensile testing machine, and the standard adopted is GB / T 37841-2019 "Test method for puncture resistance of plastic film and sheeting".

[0044] Room temperature conductivity: The room temperature conductivity is tested using a multi-channel ion conductivity test system.

[0045] As can be seen from Table 1, the solid electrolyte membranes provided by Examples 1 to 4 have a high puncture strength, indicating that the introduction of the inorganic nanofiber membrane significantly improves the mechanical strength of the material. Compared with Comparative Example 1, the membranes provided by Examples 1 to 4 have extremely high room temperature conductivity. This is because the size effect of the inorganic nanofiber membrane can reduce the crystallinity of the polymer, promote the movement of the PEO polymer chain segments, and improve the conductivity of the composite solid electrolyte membrane. And the porous structure of the inorganic nanofiber membrane is also conducive to the transmission of lithium ions and improves ionic conductivity.

[0046] Table 1

[0047] Performance Test 2: The solid electrolyte membranes prepared in the above examples and comparative examples were used to prepare solid-state lithium batteries for charge and discharge tests, including a positive electrode, a negative electrode, a shell and the composite solid electrolyte membrane obtained above. The formula of the active material layer of the positive electrode sheet is NCM811:SP:PVDF=90:3:7, and the surface density is 15 mg / cm 2 , compaction 3.2g / cm 3 The negative electrode is a lithium copper composite strip. The test results are shown in Table 2.

[0048] As shown in Table 2, compared with Comparative Example 1, the discharge specific capacity and capacity retention rate of the battery assembled with the composite solid electrolyte prepared in Examples 1 to 4 are better than those in Comparative Example 1. This is because the composite solid electrolyte of the present invention has more ion transmission channels, which improves the overall performance of the battery. In addition, the solid-state lithium battery prepared by the present invention has no flowing electrolyte and has a composite solid electrolyte membrane with good thermal stability, thereby reducing the risk of thermal runaway of the battery and improving safety performance.

[0049] Table 2

[0050] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A highly conductive composite solid electrolyte membrane, characterized in that: The highly conductive composite solid electrolyte is composed of lithium salt, an inorganic nanofiber membrane as a network skeleton, and polyethylene oxide as a polymer matrix; The thickness of the highly conductive composite solid electrolyte membrane is 20-50 μm; The lithium salt is selected from at least one of LiTFSi, LiFSi, and LiClO4; The molecular weight of the polyethylene oxide is 200000-2000000 g / mol; The inorganic nanofiber membrane has a diameter of 300-600 nm and a thickness of 15-40 μm.

2. The highly conductive composite solid electrolyte membrane according to claim 1, characterized in that: The inorganic nanofiber membrane is obtained by the following steps: The organic polymer template, the inorganic material and the solvent are mixed to obtain an electrostatic spinning solution, and electrostatic spinning is performed and calcined in an air atmosphere to obtain the inorganic nanofiber membrane.

3. The highly conductive composite solid electrolyte membrane according to claim 2, characterized in that: The organic polymer template is selected from at least one of polyvinyl alcohol and polyvinyl pyrrolidone; The inorganic material is selected from at least one of silicon dioxide, zirconium oxide and titanium dioxide; The solvent is selected from water and / or ethanol.

4. The highly conductive composite solid electrolyte membrane according to claim 2, characterized in that: In the electrospinning solution, the concentration of the organic polymer template is 6-12 wt %, and the concentration of the inorganic material is 2-4 times the concentration of the organic polymer template.

5. The highly conductive composite solid electrolyte membrane according to claim 2, characterized in that: The voltage of the electrospinning is 15-30KV; The extrusion speed of the electrospinning is 1.5-3 ml / h; The receiving distance of the electrospinning is 8 to 25 cm.

6. The highly conductive composite solid electrolyte membrane according to claim 2, characterized in that: The calcination temperature is 600-1000°C; The calcination time is 2 to 8 hours.

7. A method for preparing a highly conductive composite solid electrolyte membrane according to any one of claims 1 to 6, characterized in that: The following steps are involved: The lithium salt, polyethylene oxide and an organic solvent are mixed to obtain a membrane-forming slurry, which is then cast into an inorganic nanofiber membrane, allowed to stand, and vacuum dried to obtain the highly conductive composite solid electrolyte membrane.

8. The preparation method according to claim 7, characterized in that: The organic solvent is selected from at least one of acetonitrile and dichloromethane; In the film-forming slurry, the mass content of polyethylene oxide is 2-6 wt %, and the mass content of lithium salt is 2-6 wt %.

9. The preparation method according to claim 7, characterized in that: The vacuum drying temperature is 40-60°C; The vacuum drying time is 12 to 36 hours.

10. An application of the highly conductive composite solid electrolyte membrane according to any one of claims 1 to 6, characterized in that: For all-solid-state lithium batteries.

Citation Information

Patent Citations

  • A composite solid electrolyte with high ionic conductivity and a preparation method thereof

    CN109148944A

  • Solid-state electrolyte composite membrane, preparation method and application thereof

    CN111370753A

  • Ceramic composite solid electrolyte containing inorganic nano oxide particles, and preparation method and application thereof

    CN114976215A

Cited By

  • Electrode assembly with solid electrolyte, battery cell and manufacturing method

    CN121011709A